Indications of Understorey Management Practices impact on Vascular Plant and Arthropod Diversity in Olive Groves on Lesvos, Greece - Scheepens, Nadia; Stavrianakis, Giorgos; Komba, Raheema; Sentas, Efstratios; Kizos, Thanasis (ENTOMOLOGIA HELLENICA, 2024)
This study investigates the impact of three understorey management practices – herbicide application, understorey clearing, and undisturbed understorey – on the biodiversity of plant and arthropods in olive groves in the Gera region on Lesvos, Greece. The study found that herbicide application had a negative effect on plant diversity, but less pronounced effects on arthropods. The rapid recovery of arthropod biodiversity is likely due to the high structural complexity in the Gera region. Abandoned olive groves displayed the lowest arthropod abundance and vegetation, leading to gradual impoverishment of plant biodiversity and negative impacts on arthropod diversity. The proportion of annual species in the plant cover was positively associated with arthropod abundance. The study proposes a new eco-scheme that supports farmers for maintaining understorey plant cover, with periodical clearing through ruminant grazing, to enhance plant and arthropod biodiversity in olive grove systems.